2010
DOI: 10.1007/s00426-010-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning of timing patterns and the development of temporal expectations

Abstract: The present study investigated the learning of a culturally unfamiliar musical rhythm, leading to the development of temporal expectations, and it explored the potential for generalization across tempi and tasks. With that aim, we adapted the serial reaction time task to examine the learning of temporal structures by an indirect method. The temporal pattern employed was based on a complex interval ratio (2:3) and compared to one based on a simple interval ratio (1:2). In the exposure phase, non-musician partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…That is, we measured how well they could synchronise their movements to an external stimulus [33], [34]. For this, we used a variation of the synchronisation-continuation tapping paradigm [35], [36]. All tasks were performed by non-musicians and by pianist and brass player musicians.…”
Section: Introductionmentioning
confidence: 99%
“…That is, we measured how well they could synchronise their movements to an external stimulus [33], [34]. For this, we used a variation of the synchronisation-continuation tapping paradigm [35], [36]. All tasks were performed by non-musicians and by pianist and brass player musicians.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research, failing to find independent learning of temporal structure, instead required identification of the events presented according to the temporal structure (Buchner & Steffens, 2001;Shin & Ivry, 2002). Two studies have shown that implicit learning can occur in an identification task, but, in both instances, the temporal structures were based on a sequence of IOIs and were strongly metrical (Brandon et al, 2012;Tillmann et al, 2011; see also Schultz et al, 2013, for a discussion on identification vs. detection in auditory SRTTs). The events were syllables (e.g., BPa^, BTa^) presented according to either a simple (Tillmann et al, 2011) or complex (Brandon et al, 2012) repeating sequence of IOIs.…”
Section: Implicit Learning Of Temporal Structuresmentioning
confidence: 99%
“…However, a small number of studies using an auditory adaptation of the SRTT have demonstrated learning of temporal structure without a correlated event structure (e.g., Brandon, Terry, Stevens, & Tillmann, 2012;Schultz, Stevens, Keller, & Tillmann, 2013;Salidis, 2001, Tillmann et al, 2011. For instance, Salidis (2001) required participants to press a key every time they heard a tone.…”
Section: Implicit Learning Of Temporal Structuresmentioning
confidence: 99%
See 2 more Smart Citations